Analisis Studi Kelayakan Bisnis "Baginda Gedhang" - Nadila Kartikasari; Afrizal Miradji; Mega Afiqoh; Sinta Dewi; Akbar Ababil (Majalah Ekonomi, 2023)
ABSTRACT In the post-pandemic period, many large companies and Micro Small and Medium Enterprises (MSME) have revived, in an era like this needs are increasing, especially for food. Supported by technological advances, everything can be accessed quickly and easily. Many Gen Z are trying their luck in the businees world, therefore a new idea emerged to create a product called “Baginda Gedhang” this product is an Innovation made from bananas combined with spring roll skin. The ingredients and production process for this product are always considered to maintain the taste and quality of the product. Keywords :Banana, UMKM, Business Idea